Combination of gamma irradiation and sodium carbonate pretreatment on oil palm Empty Fruit Bunch (EFB) for high acidic hydrolysis yield - Chin, Siew Xian; Chia, Chin Hua; Sarani Zakaria,; Sahrim Hj. Ahmad,; Siti Masrinda Tasirin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Oil palm empty fruit bunch (EFB) fibres were pretreated by gamma irradiation followed by sodium carbonate (Na2CO3) before the acid hydrolysis process to produce reducing sugars using diluted sulphuric acid (H2SO4). In this study, EFB fibres were irradiated at different doses, i.e. 0, 100 and 200 kGy. Meanwhile, the gamma irradiated sample were then subjected to Na2CO3 pretreatment with 0 and 5% total titratable alkali (TTA). The effect of the pretreatment using gamma irradiation and Na2CO3 on the physical and chemical properties of the EFB fibres and the yield of the reducing sugar obtained from the acid hydrolysis process was investigated. The obtained results showed that the content of holocellulose was increased significantly with the increase of irradiation doses combined with Na2CO3 pretreatment, whereas lignin content of the EFB was decreased. The gamma irradiation and Na2CO3 pretreatment resulted in structure breakage and removal of silica of EFB fibres which can be due to the swelling of the fibres. A synergistic effect between gamma irradiation and Na2CO3 was observed, in which the yield of reducing sugars was increased by combining the gamma irradiation and Na2CO3 pretreatment.